ナンキョク ロケット S-210JA-24 25 ゴウキ ニヨル デンリソウ デンバ ノ カンソク b. デンバ ト デンリュウ ケイ ダイ1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 小川, 俊雄; オガワ, トシオ; 森田, 護; モリタ, マモル; 福西, 浩; フクニシ, ヒロシ; 松尾, 敏郎; マツオ, トシロウ; 芳野, 赳夫; ヨシノ, タケオ; OGAWA, Toshio; MORITA, Mamoru; et al. (国立極地研究所, 1979)
P(論文) 昭和基地から打ち上げられた南極ロケットS-210 JA-24,25号機を用いて,約120 kmまでの電離層電場のDCおよびAC成分(8-110 Hz)を観測した.ロケットはオーロラの縁を通過した磁気地方時真夜中付近で観測されたDC電場は,高さによらない約20mV/mの電場と,30mV/mにも達する局所的電場から成る.前者はオーロラ帯電離層に一般的に存在する大規模電場である.後者は降下オーロラ粒子による空間電荷の影響と思われる電場で,100-115 kmの高度に存在する.ロケットの上昇下降時とも,高さ96から112 kmの局限された高度領域に,強いACノイズが観測された.ノイズの周波数は高さとともに変わるが,20-110 Hz以上に及ぶ.ノイズはDC電場と直交する方向に偏波している.このようなノイズの原因は,電離層内の電流層におけるプラズマ不安定によるものと思われる. DC and AC (8-110 Hz) electric fields were observed in the auroral ionosphere up to 120 km with spherical double probes on board the sounding rockets S-210JA-24 and 25 at Syowa Station. The rockets passed close to auroras. The DC electric fields observed during substorms at magnetic midnight are composed of the height-independent electric field of about 20 mV/m and the local electric field of up to 30 mV/m. The former electric field is the large scale electric field generally existing in the auroral ionosphere, and the latter local electric field will be the effect of space charges produced by precipitating auroral particles, peaking at the heights between 100-115 km. Strong AC noises were observed in the limited altitude range of 96-112 km during both the ascent and the descent. The noise frequencies varied with altitude and were ranged between 20 and higher than 110 Hz. The noises appeared in the direction perpendicular to the DC electric field. These characteristics suggest that the noises might be generated by plasma instability in the ionospheric current layer. departmental bulletin paper